Decline in Sirtuin-1 expression and activity plays a critical role in blood-brain barrier permeability in aging - Stamatovic, Svetlana M.; Martinez-Revollar, Gabriela; Hu, Anna; Choi, Jennifer; Keep, Richard F.; Andjelkovic, Anuska V. (Neurobiology of disease, 2019)
Accumulating evidence suggest that cerebral microvascular disease increases with advancing age and is associated with lacunar stroke, leukoaraiosis, vascular dementia and Alzheimer disease. Increased blood brain barrier (BBB) permeability/leakage takes “center stage” in ongoing age-related vascular/brain parenchymal injury. Although significant effort has been made in defining the gene mutations and risk factors involved in microvascular alterations in vascular dementia and Alzheimer disease, the intra- and intercellular pathogenic mechanisms responsible for vascular hyperpermeability are still largely unknown. The present study aimed to reveal the ongoing senescence process in brain endothelial cells and its effect on BBB integrity in healthy/non-disease conditions. An analysis of BBB integrity during the life span of C56Bl6 mice (young, 2–6 months; middle-aged, 6–12, months; old, 16–22 months) showed increased BBB permeability for different molecular sized tracers (sodium fluorescein, inulin and 20 kDa dextran) in aged mice which was accompanied by modifications in tight junction (TJ) complex organization, manifested as altered TJ protein expression (particularly claudin-5). A gene screening analysis of aging associated markers in brain microvessels isolated from “aged” mice (C56Bl6, 18-20 months) and human brain samples showed a significant decline in sirtuin-1 expression (Sirt1; ~2.8-fold) confirmed at mRNA and protein levels and by activation assay. Experiments in Sirt1 transgenic mice and brain endothelial cell-specific Sirt1 knockout mice indicated that Sirt1 affects BBB integrity, with loss increasing permeability. Similarly, in vitro, overexpressing Sirt1 or increasing Sirt1 activity with an agonist (Sirt1720) protected against senescence-induced brain endothelial barrier hyperpermeability, stabilized claudin-5/ZO-1 interactions and rescued claudin-5 expression. These findings reveal a novel role of Sirt1 in modulating aging-associated BBB persistent leakage. •The “aging” of brain endothelial cells affect BBB integrity and tight junction complex stability in mouse and human.•Reduced sirtuin1 gene/protein expression and activity was found in aged brain mouse and human brain endothelial cells.